APPLICATION OF THE INTERNET OF THINGS IN SMART LAUNDRY - Safriana; Muhammad Nasir; Aswandi; Jorge O. Brusa (PT. Radja Intercontinental Publishing, 2023)
The service system for every laundry in every area is currently still done manually, this is considered less efficient because the waiters are often confused when looking for clothes that a customer wants to pick up. Then waiters sometimes forget to give information to customers to pick up clothes that have been washed. This becomes a problem where customers have to go back and forth to ask whether their clothes have been washed or not. Smart laundry is a form of implementation whose main objective is to help customers find out which clothes are ready to be picked up and can help waiters find out where the customer's clothes are. RFID tags for customers who are registered as members of the laundry service are used as a tool to store customer data when the customer brings clothes to be washed and to find out where the customer's clothes have been washed when the customer picks up the clothes. This research also uses the QoS (Quality of Service) method to measure the delay parameters produced in the network used. The results of testing that were carried out 35 times in this research resulted in a delay of 0.956458 seconds. From the test results, the maximum reading distance between the RFID tag and the RFID reader is 3 cm. From the results of 10 trials, the percentage of system success in sending notifications in the form of clothes that have been completed and ready to be picked up to customers is 80% and system failure in sending notifications is 20%.